(untitled) (Research, Society and Development, 2022)
Gestational diabetes mellitus (GDM) is defined as any degree of glucose intolerance, with a decrease in insulin sensitivity during pregnancy, with recognition in the second or third trimester of pregnancy and disappearing after delivery. This mini-review is to provide a broad view of some recent studies that investigated the placental morphology in cases of maternal diagnosis of gestational diabetes. A literature search was carried out in PubMed, Medline, Google Scholar data sources, verifying the morphological characteristics of the placenta in situations of diagnosis of gestational diabetes, through prospective and observational studies, with the key terms “gestational diabetes”, “placenta” and ‘morphological”. We show, in table format, the studies carried out between 2015 and 2020 with the main placental morphological changes that reflect the condition of pregnant women with diabetes mellitus, the most considered in the literature, increase in placental weight and thickness. It was evident that there are still few studies on placental changes, requiring the encouragement of scientific productions on the approach. In conclusion, understanding the mechanism of placental development allows the assessment of changes when pregnant women are diagnosed with GDM, taking into account therapeutic strategies that can intervene in glycemic and metabolic control, in order to ensure maternal-fetal health.